Redes de interacción plantas-aves polinizadoras en distintos tipos de cobertura vegetal del parque universitario de educación ambiental y recreación (puear) de la ciudad de Loja, Ecuador - Espinosa Guajala, Carlos Daniel (2021)
Understanding an ecosystem requires knowing not only the structure of its biodiversity, but it is also fundamental to understand the mutual interactions that are the basis for the functionality of many ecosystems. This mutualism forms a regulating ecosystem service (pollination or seed dispersal). In the pollination service with plant-pollinator bird interaction, structures are built in networks with properties for ecosystem stability (regeneration and maintenance) in the face of disturbances, through plant reproduction, food production and natural resources. This study identified and compared the structure of bird-flower interaction networks in four different types of vegetation at the PUEAR: Natural Forest, Plantations Forest, Anthropic Paramo, and Scrub. To record interactions, random transects and observation points were placed in each vegetation type, compiling the data in a presence-absence matrix for later analysis. Six indices of the network of each vegetation type were calculated: nesting, connection, modularity, robustness, asymmetry and Shannon diversity. The nesting index was higher in Scrub (0.70) compared to other vegetation types. The connection was lower in Plantations Forest (0.23). The highest modularity was in Forest Plantations (0.70). While the robustness and asymmetry were greater in Forest with 0.74 and 0.43, respectively. The vegetation types with the greatest diversity were Scrub and Plantations Forest with 2.57. At PUEAR, interactions networks varied in their number of interactions due to the availability of resources that plants offer to pollinating birds, where the vegetation types Scrub and Plantations Forest had greater availability of resources and the highest number of interactions, making them more resistant to disturbances. Keywords: interaction networks, biodiversity, bird-flower interaction, ecosystem.